Investigating the protective potential of dinoprost in a rat model of ischemia-reperfusion - Karakus, Savas; Ozkaraca, Mustafa (Annals of Medical Research, 2023)
Aim: This study investigates the protective effects of Dinoprost against Ischemia/Reperfusion (I/R) damage in the rat ovary, focusing on the expression of cyclooxygenase-2 (COX-2), Interleukin-1β (IL1β), and Tumor Necrosis Factor-α (TNF-α). Additionally, the impact of Dinoprost on reducing hemorrhage in the ovarian tissue is evaluated.Materials and Methods: A total of 24 rats were randomly divided into four groups: Control, Ischemia (Isch), I/R, and Dino+I/R. Ischemia was induced by clamping the ovarian blood supply, followed by reperfusion. Dinoprost was administered before reperfusion in the Dino+I/R group. COX-2, IL1β, and TNF-α expression levels were assessed through histochemical and immunochemical analyses. Hemorrhage in the ovarian tissue was also examined.Results: The Dino+I/R group exhibited a significant decrease in COX-2 expression compared to the Isch and I/R groups (p
Keywords: Dinoprost; Ischemia/reperfusion injury; Rat ovary; Tissue damage